Analisis Perbandingan Fonem Vokal Nomina dan Verba pada Dialek Bahasa Jawa Indramayu dengan Bahasa Jawa Solo - Tety Rukmanah; Meyliana Putri; Dona Aji Karunia Putra (LPPM STKIP PGRI Bandar Lampung, 2023)
Dialect is a variation of language that has differences in its usage. Javanese is a regional language that has many variations and is used in a wide range. This study aims to describe the comparison of vowel phonemes in the Javanese dialects of Indramayu and Solo. This research was conducted using a descriptive qualitative method with comparative techniques. The object studied in this study is the Javanese dialect of Indramayu and Solo. The data in this study are in the form of vocabulary in Indramayu and Solo Javanese. Sources of data in this study were the results of interviews with informants and vocabulary lists for Indramayu and Solo Javanese. Data collection techniques applied in this research are interview techniques, documentation techniques, observe, and note. The results showed that there were several vowel correspondences to nouns and verbs in the Javanese dialects of Indramayu and Solo. The correspondence includes differences between vowel phonemes /a/ and /o/ in Javanese verbs and nouns in Indramayu and Javanese in Solo. As in the Indramayu district which is located in West Java and the Solo City area which is located in Central Java, and many other areas that use Javanese dialects. In writing this journal, the researcher only focuses on the analysis of differences in noun and verb vowel phonemes in the Indramayu Javanese dialect and the Javanese Solo language. The results of this study will show how the differences in the Javanese dialect between the two regions have several differences in vowel phonemes in each word but have the same word meaning so that it makes each variety unique.